Otocephaly Diagnosed Prenatally: A Case Study of a Rare Congenital Defect - Konukcu, Birsen (Wiley, 2024)
BackgroundAgnathia-otocephaly complex (AOC) is a rare and complex craniofacial malformation characterized by mandibular hypoplasia or agnathia, auricular fusion, microstomia with oroglossal hypoplasia or aglossia. It has a very bad prognosis and can arise alone or in conjunction with heart defects and forebrain abnormalities.Case ReportA standard second-trimester ultrasound exam was recommended for, a 23-year-old primigravida woman who was at 22 weeks gestation. The oral fissure was pinhole-shaped, the mouth was incredibly small, and the usual lower jaw and lower lip had vanished from the S-curve. On the front of the neck were the two ears. Amniocentesis revealed a 46,XY normal karyotype. The family opted for a medically assisted termination. At 23 weeks, the pregnancy was ended by vaginal delivery. Observation of the specimen revealed that the ear placements were remarkably low, and the specimen's observation revealed that the two earlobes were joined at the front of the neck.ConclusionIdentifying the development of the mandible and locating auricles during prenatal ultrasound diagnosis was particularly challenging could be a better way to phrase this like in our recent example, the combination of two-dimensional and three-dimensional ultrasound was able to confirm the prenatal diagnosis of AOC.
Keywords: agnathia-otocephaly complex; antenatal scan; congenital disorder; microstomia; otocephalyagnathia